2015
DOI: 10.1007/s10461-015-1250-4
|View full text |Cite
|
Sign up to set email alerts
|

Anal Douche Practices and Willingness to Use a Rectal Microbicide Enema for HIV Prevention and Associated Factors Among an Internet Sample of HIV-Negative and HIV-Discordant Male Couples in the US

Abstract: A significant proportion of MSM acquire HIV from their primary relationship partners. Rectal microbicides are currently being studied to determine their efficacy for HIV prevention, yet willingness to use rectal microbicides among male couples is largely unknown. Dyadic data from 333 HIV-negative and HIV-discordant male couples, representing 631 HIV-negative men, were used to assess anal douching practices and willingness to use a rectal microbicide for HIV prevention. 17% of men douched 100% of the time befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Our study found douching is common among MSM seeking PrEP in Southern California and the odds of RI increases to 3.59 when douching at least weekly and to 5.41 for MSM with more than six male sexual partners. Like other behavioural studies on douching in Europe 15, 17 and the United States 14, 27 , we found douching to be popular among MSM engaging in ARS. We also had a high prevalence of RD (261 of 395, 66%), slightly higher than the prevalence of 14–53% found in previous studies 10, 15, 16, 28, 29 .…”
Section: Discussionsupporting
confidence: 84%
“…Our study found douching is common among MSM seeking PrEP in Southern California and the odds of RI increases to 3.59 when douching at least weekly and to 5.41 for MSM with more than six male sexual partners. Like other behavioural studies on douching in Europe 15, 17 and the United States 14, 27 , we found douching to be popular among MSM engaging in ARS. We also had a high prevalence of RD (261 of 395, 66%), slightly higher than the prevalence of 14–53% found in previous studies 10, 15, 16, 28, 29 .…”
Section: Discussionsupporting
confidence: 84%
“…Of MSM who douche, 79 to 93% report using non-commercial/homemade substances and solutions. (2, 9, 13) Among them, water is by far most commonly used (64 to 82% of douchers who use non-commercial products), (2, 3, 9, 14) followed by water and soap (11 to 29.6%), (2, 9, 13) and water and salt (4.7 to 10.6%) (2, 9, 13). Between 11 and 31% of MSM who douche rectally report using commercial products (2, 9, 13), with saline-based solutions being the most common (56 to 100% of rectal douchers who use commercial products).…”
Section: Resultsmentioning
confidence: 99%
“…Prior research suggests that partner type (e.g., hookup, friend with benefits, romantic partner) might affect likelihood of sexual roles and influence risk reduction negotiation (e.g., condom use) (2223), as well as their willingness to use a RM during sex in the future (24). Taken together, these findings suggest the need to extend the RM agenda to include partner-level studies (25). By examining dyadic relationships, we might be able to identify key relational characteristics that promote gel use and inform the development of partner-level interventions to promote RM product acceptability, use, and adherence.…”
Section: Discussionmentioning
confidence: 87%